The Effect of Behavioral Ivan Pavlov Conselvation using Modeling Techniques Through Lesson Study to Improve of arranging work neatly Students of Class X Ap2 State 2 State Vocational School 2 Singaraja - Anak Agung Gede Agung Darma Putra; Ni Ketut Suarni; I Ketut Dharsana (RedwhitePress)
The purpose of this study was to determine the effect of behavioral counseling Ivan Pavlov with modeling techniques to improve the character of arranging work neatly. This type of research is quasi-experiment with pretest-posttest control Group design. The research sample was 36 first-grade. Data collection uses a arranging work neatly questionnaire. It is proven by the value of tcount 2.472 > ttable 2.03. So that Ho is rejected and Ha is accepted. So there are significant differences. It was concluded that Ivan Pavlov's behavioral counseling with effective modeling techniques to improve the character of arranging work neatly.